Spatio-temporal regulation of nuclear division by Aurora B kinase Ipl1 in Cryptococcus neoformans. - Neha Varshney; Subhendu Som; Saptarshi Chatterjee; Shreyas Sridhar; Dibyendu Bhattacharyya; Raja Paul; Kaustuv Sanyal (PLoS Genetics, 2019)
The nuclear division takes place in the daughter cell in the basidiomycetous budding yeast Cryptococcus neoformans. Unclustered kinetochores gradually cluster and the nucleus moves to the daughter bud as cells enter mitosis. Here, we show that the evolutionarily conserved Aurora B kinase Ipl1 localizes to the nucleus upon the breakdown of the nuclear envelope during mitosis in C. neoformans. Ipl1 is shown to be required for timely breakdown of the nuclear envelope as well. Ipl1 is essential for viability and regulates structural integrity of microtubules. The compromised stability of cytoplasmic microtubules upon Ipl1 depletion results in a significant delay in kinetochore clustering and nuclear migration. By generating an in silico model of mitosis, we previously proposed that cytoplasmic microtubules and cortical dyneins promote atypical nuclear division in C. neoformans. Improving the previous in silico model by introducing additional parameters, here we predict that an effective cortical bias generated by cytosolic Bim1 and dynein regulates dynamics of kinetochore clustering and nuclear migration. Indeed, in vivo alterations of Bim1 or dynein cellular levels delay nuclear migration. Results from in silico model and localization dynamics by live cell imaging suggests that Ipl1 spatio-temporally influences Bim1 or/and dynein activity along with microtubule stability to ensure timely onset of nuclear division. Together, we propose that the timely breakdown of the nuclear envelope by Ipl1 allows its own nuclear entry that helps in spatio-temporal regulation of nuclear division during semi-open mitosis in C. neoformans.